A Diffusion-based Model of Doxorubicin Release from Liposomes: Effects of Size and Membrane Permeability - Gregoria Illya (BULETIN FISIKA, 2025)
Liposomes are widely used as nanocarriers in cancer therapy due to their ability to encapsulate chemotherapeutic agents and modulate drug release. Among these, doxorubicin-loaded liposomes, such as Doxil®, have demonstrated enhanced safety and efficacy profiles. However, predicting the kinetics of drug leakage remains critical for optimizing liposome design and therapeutic performance. In this study, a first-order mathematical model based on Fick’s law of diffusion was developed to predict the leakage kinetics of doxorubicin from liposomes. The model captures key behaviors, including the effects of liposome size and lipid composition on membrane permeability and leakage. Simulations show that lower permeability coefficients, associated with increased membrane rigidity, slow down drug leakage, whereas smaller liposomes exhibit faster leakage due to their higher surface-area-to-volume ratios. Despite its simplicity, the model successfully captures experimental trends, reproduces permeability coefficients on the same order of magnitude as those observed in other doxorubicin-loaded liposomal systems, and demonstrates robustness to minor structural variations. It serves as a practical tool for early-stage design of liposomal drug delivery systems and highlights the sensitivity of drug leakage to key formulation parameters.